Determinants of Customer Satisfaction at Starbucks Coffee Outlets in Denpasar - Jaya, Putu Primayana Surya; Martini, Ida Ayu Oka (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The significance of customer happiness in business lies in its substantial influence on the enduring prosperity of a company. The primary objective of this study is to examine and evaluate the mediating effect of purchasing decisions in relation to the elements that impact consumer satisfaction, specifically brand equity and product quality. The present study employs a descriptive quantitative methodology, focusing on all Starbucks coffee establishments in Denpasar. The participants of this study consisted of consumers from eight Starbucks coffee establishments located throughout the city of Denpasar. The selection of participants was conducted using a simple random sampling method. The data collection methodology employs a Google Form using an interval scale ranging from one to ten points. The present study employs the Structural Equation Model (SEM) technique, explicitly using the Path Analysis path approach for data analysis. The clever PLS program is employed for this purpose. The findings of this study indicate that the factors of brand equity and product quality exert a favorable and statistically significant impact on consumer satisfaction, either partially or via intermediaries, in the purchasing decision process. The purchase decision variable effectively acts as a mediator in the indirect impact of brand equity and product quality on customer happiness, albeit with a weaker mediating effect compared to the direct influence.